EFFECT OF SOWING DATES IN RELATION TO INTEGRATED NITROGEN MANAGEMENT ON GROWTH, YIELD AND QUALITY OF RABI MAIZE (Zea Mays L.) - N. K. Verma; B. K. Pandey; U. P. Singh; M. D. Lodhi (Journal of Animal and Plant Sciences, 2012)
A field experiment was conducted during rabi season of 2006-07 and 2007-08 to study the effect of sowing dates and integrated nutrient management on growth, yield and quality of winter maize. The trial was laid out in split plot design with three replications, assigning total 27 treatment combinations i.e. three sowing dates (15 Oct, 25 Oct and 5 Nov) in main plots and three levels of nitrogen from inorganic fertilizer urea (50, 100 and 150 N20 kg ha-1) and two organic fertilizer (FYM, Azospirillum) and control in sub plots. The crop sown on 25 Oct significantly enhanced the growth and grain yield than early sowing 15 Oct and late sowing 5 Nov While, 150 kg of N2O ha-1 application significantly increased over 100 and 50 kg N2O ha-1. However, N2O application through FYM was found statistically at par with N2O application through the Azospirillum in growth and grain yield during both years. But, application of 100 kg ha-1 with 7.50 t ha-1 FYM at the sowing of 25 Oct significantly influenced the growth, yield and quality of maize and was recorded 9.35 and 23.07 percent more grain yield over the other treatment combinations.
Keywords: Winter maize; sowing dates; INM; growth; yield.